Efek kondisi pH asam dan basa terhadap sifat mekanis film berbasis whey-konnyaku - Fahrullah Fahrullah; Azhary Noersidiq; Hasma Hasma; Vebera Maslami (AGROINTEK, 2024)
Edible film has considerable potential as a food coating material for enhancing freshness, safety, and storage of different food products. Its advantages make it a suitable replacement for synthetic plastic packaging and a possible alternative for biodegradable materials. The research aims to observe the effect of acidic and alkaline pH on the mechanical properties of the whey-konjac film. The mechanical properties of the whey-konjac film were investigated using an experimental method. The research was conducted in a acompletely randomized design with three treatments, The treatment used different pH (P1: Control; P2: acidic condition/pH4 and P3: alkaline condition/pH 10). The values of thickness and water vapor transmission rate did not give a significant value (P0,05), value of elongation and tensile strength gave a significant value (P0,05). The mechanical properties of whey-konjac film showed that thickness was at 0,0343-0,0357 mm; the elongation was at 47,88-62,68%; the tensile strength was at 6,86-11,16 N; the water vapor transmission rate was at 6,99-7,47 g/mm-2.day-1. Films in acidic conditions can improve an excellent  cross-sectional structure of the film (flat surface and homogeneous), and films in alkaline conditions can improve thickness, elongation, and reasonable water vapor transmission rates.